Effect of conjugated linoleic acid on oocyte quality in female cd-1 mice - Gandeaga-Flores, Iván; Meza-Villalvazo, Victor Manuel; Sánchez-Ocampo, Paul; Capataz-Tafur, Jacqueline; Aguirre-Cruz, Andrés (Ecosistemas y Recursos Agropecuarios, 2020)
The objective of the present study was to evaluate the effect of conjugated linoleic acid on the quality and accumulation of lipids in oocytes of mice of the CD-1 strain. The females were distributed in two groups: control (TCON: n: 5) and conjugated linoleic acid (TCLA: n: 5), they were fed during 21 days. 53 h after treatment were sacrificed for the recovery of the oocytes, which were stained with Nile Red and observed under fluorescence. The TCLA group presented 25% more recovered oocytes compared to TCON, with 63% of oocytes of excellent and good quality (p ≤ 0.05), the lipid concentration in the TCLA group was lower (145.8 ± 17.8) compared to TCON (246 ± 13.1) (p < 0.05). The addition of conjugated linoleic acid in the diet of female CD-1 mice increases the number and quality of oocytes and decreases the accumulation of lipids in them.